Pre-treatment VD levels and VDR receptors as potential predictors of occurrence and overall survival in paediatric patients with solid tumours-a single institution pilot study - Bienertová-Vašků, Julie; Drábová, Klára; Zlámal, Filip; Tomandl, Josef; Kýr, Michal; Šplíchal, Zbyněk; Štěrba, Jaroslav (Tumour biology, 2016)
Recently, vitamin D has been recognized as an important player in the immune system, and multiple studies suggested its involvement in cancer, too. The aims of this study were to investigate selected single nucleotide polymorphisms (SNPs) in the VDR gene, BsmI (rs1544410; A > G), FokI (rs 2228570; C > T), TaqI (rs731236; T > C), ApaI (rs 7975232; C > T) and Cdx-2 (rs11568820; A > G), and to evaluate their possible predictive role for outcomes in patients with paediatric solid tumours. A total of 111 children with paediatric solid tumours were enrolled at the Department of Paediatric Oncology, University Hospital Brno (Brno, Czech Republic) along with a control population of 787 adults; all study subjects were available for genotyping of selected SNPs, and the prediagnostic levels of 25-hydroxycholecalciferol (25(OH)D3) and 1,25-dihydroxycholecalciferol (1,25(OH)2D3) were measured in the cases, too. In FokI, the heterozygote CT genotype was weakly associated with a decreased risk of paediatric solid cancer occurrence 0.82 (0.53-1.28), while the CC genotype was associated with a decreased risk of 0.58 (0.30-1.09), p = 0.09. The 1,25(OH)2D3 prediagnostic levels were indicative of the overall survival in the cases (β = -0.012, HR 0.988, 95 % CI (0.978-0.998), while higher prediagnostic levels of 1,25(OH)2D3 were associated with a statistically significant increase in overall mortality. We observed multiple effects of the alleles of the investigated polymorphisms and of 1,25(OH)2D3 on overall survival, regardless of the underlying disease.
Keywords: alely; Polymorphism, Single Nucleotide; Gene; Humans; genetické asociační studie; Receptors, Calcitriol; dítě; Child; jednonukleotidový polymorfismus; Female; frekvence genu; Alleles; Genotype; lidé; Overall survival; Vitamin D; pilotní projekty; Pilot Projects; předškolní dítě; Childhood cancer; ženské pohlaví; Genetic Association Studies; Male; receptory kalcitriolu; VDR; Adolescent; genetická predispozice k nemoci; Genetic Predisposition to Disease; Neoplasms; Gene Frequency; nádory; genotyp; mužské pohlaví; Child, Preschool; vitamin D; mladiství; SNP